Core-shell structured catalysts, methods of making and using the same, and methods of glycerol synthesis of 1,3-propanediol
Patent Information
- Application Number
- CN202510557523.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
AI Technical Summary
[0025](1)本发明提供的核壳结构催化剂具有以含W双金属氧化物以及Pt纳米颗粒作为活性组分的多层核壳结构,外壳采用TiO2纳米薄膜对活性组分起到固定作用,具有更加稳定的结构,避免活性组分的聚集和流失,能够提高催化剂的水热稳定性;
Smart Images

Figure CN122999189A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst material synthesis, specifically to a core-shell structured catalyst, its preparation method and application, and a method for synthesizing 1,3-propanediol from glycerol. Background Technology
[0002] 1,3-Propanediol is a crucial monomer for the production of poly(1,3-propanediol) terephthalate (PTT). This material combines the advantages of polyethylene terephthalate (PET) and polybutylene terephthalate (PET) and is widely used in the production of high-end polymeric products such as medical devices, premium carpets, and sportswear. Glycerin, a major byproduct of biodiesel production (accounting for approximately 10%), can be selectively synthesized into high-value-added 1,3-propanediol. This not only solves the utilization problem of glycerin but also produces high-end polymeric materials, offering advantages of being green, environmentally friendly, and sustainable. Therefore, the pathway for synthesizing high-value-added 1,3-propanediol from biodiesel byproduct glycerin is of significant importance.
[0003] Traditional industrial production methods for 1,3-propanediol, such as Shell's ethylene oxide carbonylation hydrogenation method and Degussa and DuPont's acrolein hydration hydrogenation method, have been discontinued due to complex processes, harsh reaction conditions, and environmental pollution, leading to a supply shortage of 1,3-propanediol. Although DuPont (CN200380104657.2) disclosed a method for converting sugar sources into 1,3-propanediol through bio-fermentation, this requires the addition of expensive vitamin B12, resulting in high costs. Another method for converting glycerol into 1,3-propanediol through bio-fermentation (Appl. Microbiol. Biotechnol. 1992, 36, 592-597), while reported, suffers from low conversion efficiency due to the influence of biological metabolic activity, and the product contains impurities such as vitamins and salts, with extremely high separation energy consumption.
[0004] Based on the above problems, the direct hydrogenolysis of glycerol to produce 1,3-propanediol provides a more optimized method and pathway for high-value-added conversion and upgrading. However, current catalysts have two key problems: (1) The catalysts with better activity are mainly composed of W and Pt as the main active components, but in this reaction system, due to water as a solvent, Pt is prone to agglomeration and loss under hydrothermal reaction conditions, leading to catalyst deactivation. (2) The hydrogen spillover capacity is weak, and the activity is low. Therefore, how to improve both the activity and stability of the catalyst at the same time has become the main problem that needs to be solved. Summary of the Invention
[0005] The purpose of this invention is to overcome the problems of low activity and poor stability of existing catalysts for the synthesis of 1,3-propanediol in hydrothermal reactions, and to provide a core-shell catalyst, its preparation method and application, and a method for synthesizing 1,3-propanediol from glycerol. This catalyst has a core-shell structure, and the TiO2 nanofilm in the outer shell can enhance hydrogen overflow and stabilize the Pt nanoparticles in the interlayer while maintaining high mass transfer efficiency of the glycerol feedstock, thereby improving the activity and stability of the catalyst.
[0006] To achieve the above objectives, a first aspect of the present invention provides a core-shell structured catalyst, wherein the catalyst comprises a core, a sandwich layer, and a shell;
[0007] The catalyst has a core containing a W-containing bimetallic oxide, an interlayer containing Pt nanoparticles, and an outer shell containing a TiO2 nanofilm.
[0008] Preferably, the W-containing bimetallic oxide comprises a W oxide and a first metal oxide.
[0009] Preferably, the first metal oxide is selected from at least one of aluminum oxide, zirconium oxide, and niobium oxide.
[0010] Preferably, the average particle size of the catalyst core is 0.1-10 μm, more preferably 0.2-2 μm.
[0011] Preferably, the W oxide content is 0.5-10 wt% by mass, more preferably 2-6 wt%, based on the total mass of the catalyst.
[0012] Preferably, the average particle size of the Pt nanoparticles in the interlayer is 0.5-6 nm, and more preferably 2-4 nm.
[0013] Preferably, the Pt nanoparticles have a mass percentage content of 0.2-4 wt%, more preferably 1-2 wt%, based on the total mass of the catalyst.
[0014] Preferably, the thickness of the TiO2 nanofilm of the outer shell is 0.1-80 nm, and more preferably 5-50 nm.
[0015] Preferably, the TiO2 nanofilm has mesoporous structures.
[0016] Preferably, the average pore size of the TiO2 nanofilm is 2-12 nm, and more preferably 6-10 nm.
[0017] A second aspect of the present invention provides a method for preparing a core-shell structured catalyst, wherein the method includes:
[0018] (1) Load W onto the first metal hydroxide and perform a first heat treatment to obtain a W-containing bimetallic oxide;
[0019] (2) Load Pt nanoparticles onto W-containing bimetallic oxides to obtain W-containing bimetallic oxides loaded with Pt nanoparticles.
[0020] (3) Mix the W-containing bimetallic oxide loaded with Pt nanoparticles with the interface assembly solution to carry out the synthesis reaction to obtain the intermediate product, and calcine the intermediate product to obtain the core-shell structure catalyst with TiO2 nanofilm shell.
[0021] A third aspect of the present invention provides a catalyst prepared by the method described in the second aspect.
[0022] The fourth aspect of this invention provides the use of the catalyst described in the first or third aspect in the synthesis of 1,3-propanediol.
[0023] The fifth aspect of the present invention provides a method for synthesizing 1,3-propanediol from glycerol, wherein the method comprises: contacting glycerol and hydrogen in the presence of the catalyst described in the first or third aspect to carry out a hydrogenolysis reaction.
[0024] The beneficial effects achieved through the above technical solution are as follows:
[0025] (1) The core-shell structure catalyst provided by the present invention has a multi-layer core-shell structure with W-containing bimetallic oxide and Pt nanoparticles as active components. The outer shell is made of TiO2 nanofilm to fix the active components, which has a more stable structure, avoids the aggregation and loss of active components, and can improve the hydrothermal stability of the catalyst.
[0026] (2) In this invention, preferably, the TiO2 nanofilm is an ordered mesoporous TiO2 nanofilm. Compared with films composed of conventional TiO2 nanoparticles, it has a higher mass transfer efficiency. Glycerol raw material can easily pass through the shell and reach the active sites of the core and interlayer, resulting in higher activity. The TiO2 nanofilm itself has a high hydrogen overflow capacity, which can overflow the active hydrogen of the interlayer Pt nanoparticles to the entire inner surface of the catalyst, thereby significantly improving the activity of the catalyst and resulting in a high conversion rate of the reactant glycerol. Attached Figure Description
[0027] Figure 1 This is a transmission electron microscope image of the core-shell structured catalyst from Example 1;
[0028] Figure 2 This is a scanning electron microscope image of the core-shell structured catalyst from Example 1. Detailed Implementation
[0029] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0030] The first aspect of the present invention provides a core-shell structured catalyst, wherein the catalyst comprises a core, a sandwich layer and a shell;
[0031] The catalyst has a core containing a W-containing bimetallic oxide, an interlayer containing Pt nanoparticles, and an outer shell containing a TiO2 nanofilm.
[0032] In this invention, the innermost layer of the core-shell structure catalyst is the core, the middle interlayer covers the core, and the interlayer is covered by the outermost shell. The core-shell structure catalyst of this invention has a more stable structure and higher hydrothermal stability. The interlayer uses Pt nanoparticles as the active component, and the outer shell is coated with a TiO2 nanofilm to fix the active component, preventing its aggregation and loss.
[0033] According to the present invention, preferably, the W-containing bimetallic oxide comprises a W oxide and a first metal oxide.
[0034] According to the present invention, preferably, the first metal oxide is selected from at least one of alumina, zirconium oxide, and niobium oxide. In this invention, selecting the above-mentioned metal oxide in combination with the W oxide can provide higher dispersion of the W oxide and improve catalyst selectivity.
[0035] According to the present invention, preferably, the average particle size of the core of the catalyst is 0.1-10 μm, for example, 0.1 μm, 0.2 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 5 μm, 7 μm, 10 μm, or any range between the two, preferably 0.2-2 μm. The average particle size of the core refers to the average particle size of the core particles, which can be a single particle or a particle aggregate formed by the aggregation of several small particles.
[0036] In this invention, the average particle size of the catalyst core is measured using scanning electron microscopy (SEM). The average value is obtained by randomly measuring the size of 100 core particles using NanoMeasurer software. During the measurement process, the size of a core particle is the straight-line distance connecting the two farthest endpoints of the particle in the electron micrograph. The average particle size has the conventional interpretation in the art, referring to the particle size; for spherical particles, it refers to the diameter of the sphere; for irregular particles, it refers to the largest straight-line distance within the particle.
[0037] According to the present invention, preferably, the W oxide content, based on the total mass of the catalyst, is 0.5-10 wt%, for example, 0.5 wt%, 0.6 wt%, 0.8 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 9 wt%, 10 wt%, or any range between the two, preferably 2-6 wt%. In this invention, if the W oxide content is too low, it cannot provide sufficient active sites, resulting in low catalyst activity; if the W oxide content is too high, it will lead to W oxide agglomeration and low selectivity.
[0038] In this invention, preferably, the mass percentage of the first metal oxide is 50-90 wt%, more preferably 60-80 wt%, based on the total mass of the catalyst.
[0039] According to the present invention, preferably, the average particle size of the Pt nanoparticles in the interlayer is 0.5-6 nm, for example, 0.5 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 6 nm, or any range between the two, preferably 2-4 nm. In the present invention, the average particle size of the Pt nanoparticles is measured by transmission electron microscopy (TEM), and the average value is taken from the particle size of 100 randomly measured Pt nanoparticles in the TEM image.
[0040] In this invention, the average particle size of the Pt nanoparticles meets the above-mentioned range limit, the Pt nanoparticles have better loading stability, can be uniformly dispersed on the core surface, and improve the catalytic activity of the catalyst.
[0041] According to the present invention, preferably, the Pt nanoparticles have a mass percentage content of 0.2-4 wt% based on the total mass of the catalyst, for example, 0.2 wt%, 0.4 wt%, 0.6 wt%, 0.8 wt%, 1 wt%, 1.2 wt%, 1.4 wt%, 1.6 wt%, 1.8 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, or any range between the two, preferably 1-2 wt%.
[0042] In this invention, the mass percentage of W oxide, first metal oxide, and Pt nanoparticles in the core-shell structure catalyst is obtained by ICP testing.
[0043] In this invention, the catalyst is loaded with W oxide and Pt nanoparticles on the surface of a first metal oxide. The W oxide and Pt nanoparticles are uniformly dispersed on the surface of the first metal oxide. The W oxide provides highly dispersed W active sites. Both serve as active components to improve the catalytic activity of the catalyst.
[0044] According to the present invention, preferably, the thickness of the TiO2 nanofilm of the outer shell is 0.1-80 nm, for example, 5 nm, 10 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, or any range between the two, preferably 5-50 nm, more preferably 10-40 nm. This preferred embodiment is more conducive to forming a stable multilayer core-shell structure, fixing the interlayer active components, and improving the hydrothermal stability of the catalyst.
[0045] In this invention, the thickness of the TiO2 nanofilm is obtained by transmission electron microscopy. The thickness of the nanofilm at 30 random locations in the transmission electron microscope image is measured, and the average value is taken.
[0046] According to the present invention, preferably, the TiO2 nanofilm has mesoporous structure. In this invention, the TiO2 nanofilm has an ordered mesoporous structure, which fixes the W oxide and Pt nanoparticles, improves the stability of the catalyst, and prevents the aggregation and loss of active components. Compared with films composed of conventional TiO2 nanoparticles, it has higher mass transfer efficiency, allowing glycerol feedstock to more easily penetrate the shell and reach the active sites in the interlayer and core, resulting in higher catalytic activity.
[0047] According to the present invention, preferably, the average pore size of the TiO2 nanofilm is 2-12 nm, for example, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, or any range between the two, preferably 6-10 nm. In the present invention, it can be seen from the scanning electron microscope image of the core-shell structure catalyst that the catalyst shell has an ordered pore size TiO2 nanofilm.
[0048] In this invention, the average pore size of the TiO2 nanofilm was measured by low-temperature nitrogen adsorption method.
[0049] A second aspect of the present invention provides a method for preparing a core-shell structured catalyst, wherein the method includes:
[0050] (1) Load W onto the first metal hydroxide and perform a first heat treatment to obtain a W-containing bimetallic oxide;
[0051] (2) Load Pt nanoparticles onto W-containing bimetallic oxides to obtain W-containing bimetallic oxides loaded with Pt nanoparticles.
[0052] (3) Mix the W-containing bimetallic oxide loaded with Pt nanoparticles with the interface assembly solution to carry out the synthesis reaction to obtain the intermediate product, and calcine the intermediate product to obtain the core-shell structure catalyst with TiO2 nanofilm shell.
[0053] In this invention, the core-shell structured catalyst prepared by the above method can form a stable multilayer core-shell structure. The TiO2 nanofilm of the outer shell plays a role in fixing the active components Pt and W oxides. The preparation method conditions are easy to control, and the resulting catalyst has good hydrothermal stability and good catalytic activity.
[0054] According to the present invention, preferably, the first metal hydroxide is selected from at least one of aluminum hydroxide, niobium hydroxide and zirconium hydroxide.
[0055] According to the present invention, the loading method is not particularly limited, and those skilled in the art can choose conventional loading methods. Preferably, in step (1), the loading method includes: coating the W precursor onto a first metal hydroxide, performing a first heat treatment to obtain a W-containing bimetallic oxide.
[0056] According to the present invention, the W precursor is a conventional tungsten-containing compound in the art, and preferably, the W precursor is selected from at least one of ammonium metatungstate, ammonium paratungstate, and sodium tungstate.
[0057] According to the present invention, preferably, the amount of the W precursor added is calculated as WO3, the amount of the first metal hydroxide used is calculated as oxide, and the ratio of the amount of the W precursor to the amount of the first metal hydroxide used is 1:5-50, for example 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, or any range between the two, preferably 1:10-30.
[0058] According to the present invention, preferably, the conditions for the first heat treatment include: a heating temperature of 100-900°C, more preferably 500-600°C; and a heating time of 1-8 hours, more preferably 2-4 hours. Performing the first heat treatment under the above conditions enables the W oxide to be uniformly loaded onto the core surface, forming highly dispersed W active sites.
[0059] According to the present invention, preferably, in step (2), the loading method includes: mixing a W-containing bimetallic oxide and a Pt-containing nanoparticle solution and performing a second heat treatment to obtain a W-containing bimetallic oxide loaded with Pt nanoparticles.
[0060] According to the present invention, the source of the Pt-containing nanoparticle solution is not particularly limited. Preferably, the preparation method of the Pt-containing nanoparticle solution includes: mixing a Pt source, a first template agent, and a first solvent, and refluxing the mixture to obtain the Pt nanoparticle solution.
[0061] According to the present invention, preferably, the amount of Pt source used is based on Pt element, and the mass ratio of Pt source: first template agent: first solvent is (1-5):(5-50):(500-10000), more preferably (2-4):(10-30):(1000-5000). Adding the above substances according to the above amounts enables the preparation of a Pt nanoparticle solution with a more uniform average particle size distribution.
[0062] According to the present invention, preferably, the reflux conditions include: a reflux temperature of 60-200°C, preferably 80-180°C, under a protective atmosphere; and a reflux time of 0.5-6 h, preferably 2-4 h. Reflux under these conditions yields Pt nanoparticles with a more uniform average particle size distribution and a stable Pt nanoparticle solution.
[0063] In this invention, the type of protective atmosphere is not particularly limited, but is preferably selected from at least one of argon, nitrogen and helium.
[0064] According to the present invention, the type of platinum source is not particularly limited and can be any conventional platinum-containing compound that can provide Pt in the art. Preferably, the Pt source is selected from at least one of chloroplatinic acid, tetraammineplatinum nitrate and potassium chloroplatinate.
[0065] According to the present invention, preferably, the first template agent is selected from at least one of polyvinylpyrrolidone, polyethyleneimine and oleylamine.
[0066] According to the present invention, the type of the first solvent is not particularly limited. Preferably, the first solvent is selected from at least one of water, a saturated monohydric alcohol having 1-3 carbon atoms, and a saturated dihydric alcohol having 1-3 carbon atoms. The solvent is selected from at least one of an aqueous methanol solution, an aqueous ethanol solution, and an aqueous propanol solution. More preferably, the solvent is water and ethanol, wherein the volume ratio of water to ethanol is not particularly limited.
[0067] According to the present invention, preferably, the mass ratio of the W-containing bimetallic oxide to the Pt nanoparticles is 1:0.002-0.04, for example 1:0.002, 1:0.004, 1:0.006, 1:0.008, 1:0.01, 1:0.02, 1:0.03, 1:0.04, or any range between the two, preferably 1:0.01-0.02. Using the above Pt nanoparticle solution, the synthesized catalyst exhibits controllable Pt nanoparticle size, uniform distribution, and higher activity and selectivity.
[0068] According to a preferred embodiment of the present invention, step (2) further includes mixing under ultrasonic and stirring conditions. The present invention does not specifically limit the ultrasonic and stirring conditions in step (2), which can be appropriately selected according to specific circumstances. The stirring rate is not particularly limited, as long as it achieves uniform mixing. In the present invention, the method of adding each substance in step (2) is not particularly limited; they can be added separately or together.
[0069] Preferably, this invention further includes a process of separating the ultrasonic products and then subjecting them to a second heat treatment. The separation method is not particularly limited; according to a specific embodiment of the invention, centrifugal separation can be used. The conditions for centrifugal separation are not particularly limited and can be adjusted adaptively by those skilled in the art based on the separation situation. Preferably, the ultrasonic products are mixed with a hydrochloric acid solution and then centrifuged, followed by washing of the centrifuged products. Preferably, a mixed solution of acetone and n-hexane is used for washing; the mass ratio of acetone to n-hexane is not particularly limited and can be adjusted adaptively by those skilled in the art.
[0070] According to the present invention, preferably, the conditions for the second heat treatment include: a heating temperature of 40-120°C, more preferably 60-100°C; and a heating time of 1-15 hours, more preferably 3-10 hours.
[0071] According to the present invention, preferably, in step (3), the intermediate product is synthesized by a confined interface single-micromicelle assembly method. In the present invention, the intermediate product synthesized by the above method, after calcination, forms a catalyst shell containing an ordered mesoporous TiO2 nanofilm, resulting in higher mass transfer efficiency and higher catalytic activity of the catalyst.
[0072] According to the present invention, preferably, the interface assembly solution comprises a second template agent, a first acid, a second acid, a titanium source, and a second solvent.
[0073] According to the present invention, preferably, in the interface assembly solution, the mass ratio of the second template agent: the first acid: the second acid: the titanium source: the second solvent is 1:(0.1-10):(0.1-10):(0.1-10):(1-100), more preferably 1:(1-3):(1-5):(0.5-7):(2-50).
[0074] According to the present invention, the type and source of the second template agent are not particularly limited, and it is a template agent conventionally used in confined interface single-micromicelle assembly methods. Preferably, the second template agent is selected from at least one of polyoxyethylene polyoxypropylene ether, polyoxyethylene-polyoxybutene ether, and polyoxyethylene-polyoxyethylene-polyoxypropylene.
[0075] In this invention, preferably, the first acid is acetic acid and / or citric acid. The addition of the aforementioned weak organic acid provides a mild acidic environment for the interfacial assembly solution.
[0076] In this invention, preferably, the second acid is concentrated hydrochloric acid and / or concentrated nitric acid. In this invention, the addition of the aforementioned strong acid further adjusts the interfacial assembly solution to an acidic environment.
[0077] According to the present invention, the type of titanium source is not particularly limited and can be a conventional titanium-containing compound. Preferably, the titanium source is selected from at least one of tetrabutyl titanate, tetraethyl titanate, and tetraoctyl titanate.
[0078] In this invention, preferably, the second solvent is selected from at least one of tetrahydrofuran, 2-methyltetrahydrofuran, and cyclopentyl methyl ether.
[0079] According to a preferred embodiment of the present invention, a second template agent, acetic acid, concentrated hydrochloric acid, titanium source and a second solvent are mixed, stirred thoroughly, and the second solvent is evaporated to obtain a template agent / TiO2 composite monomer micelle gel.
[0080] In this invention, preferably, the above-mentioned gel and tricresylbenzene are dispersed in a mixed solvent to form a transparent interfacial assembly solution. The mixed solvent comprises anhydrous ethanol and glycerol. In this invention, the amount of tricresylbenzene and the mixed solvent used is not particularly limited, as long as it is sufficient to form a transparent interfacial assembly solution.
[0081] According to a preferred embodiment of the present invention, the amount of trimethylbenzene used is 0.5-4 mL, based on 1 g of the template agent / TiO2 composite monomer micelle gel.
[0082] According to a preferred embodiment of the present invention, based on 1 g of the template agent / TiO2 composite monomer micelle gel, the amount of the mixed solvent used is 2-10 mL. The volume ratio of anhydrous ethanol to glycerol in the mixed solvent is 0.5-2:1.
[0083] In this invention, preferably, the interface assembly solution is mixed with anhydrous ethanol containing a W-containing bimetallic oxide loaded with Pt nanoparticles to carry out the synthesis reaction. The mass ratio of the interface assembly solution to the W-containing bimetallic oxide containing Pt nanoparticles is not particularly limited, such that the thickness of the TiO2 nanofilm of the catalyst shell is 0.1-80 nm, preferably 5-50 nm.
[0084] According to the present invention, preferably, the synthesis conditions include: a reaction temperature of 80-180℃, more preferably 100-160℃; and a reaction time of 2-12 h, more preferably 4-8 h. In the present invention, preferably, the synthesis reaction is carried out under stirring conditions. The stirring rate is not particularly limited, but is preferably 100-400 rpm.
[0085] In this invention, preferably, the method includes cooling the synthetic reaction product to room temperature and then centrifuging and drying it.
[0086] According to the present invention, preferably, the calcination conditions include: a calcination temperature of 200-600℃, preferably 300-500℃, under a protective atmosphere; and a calcination time of 1-10h, preferably 3-6h. In the present invention, calcination removes the template agent and improves the degree of crystallinity.
[0087] A third aspect of the present invention provides a catalyst prepared by the method described in the second aspect.
[0088] The fourth aspect of this invention provides the use of the catalyst described in the first or third aspect in the synthesis of 1,3-propanediol.
[0089] In this invention, the above-mentioned core-shell structured catalyst is used in the reaction of glycerol to synthesize 1,3-propanediol. The catalyst has good hydrothermal stability, high conversion rate of the reactant glycerol, and high selectivity for the product 1,3-propanediol.
[0090] The fifth aspect of the present invention provides a method for synthesizing 1,3-propanediol from glycerol, wherein the method comprises: contacting glycerol and hydrogen in the presence of the catalyst described in the first or third aspect to carry out a hydrogenolysis reaction.
[0091] In this invention, the above-mentioned catalyst is used to synthesize 1,3-propanediol from glycerol. The catalyst has high reactivity, high feed conversion rate, and high selectivity for the target product, which can meet the requirements of long-term operation.
[0092] According to the present invention, preferably, the reaction conditions include: a reaction temperature of 120-200°C, more preferably 130-170°C, and a hydrogen pressure of 1-6 MPa, more preferably 3-5 MPa;
[0093] And / or, the reaction conditions include: a reaction time of 4-500 h, preferably 8-360 h.
[0094] According to the present invention, preferably, the glycerol is added in the form of an aqueous glycerol solution, wherein the concentration of glycerol in the aqueous glycerol solution is 10-90 wt%, preferably 30-80 wt%.
[0095] According to the present invention, the apparatus for the reaction is not particularly limited, as long as it can achieve the hydrogenolysis reaction conditions. Preferably, the reaction activity and stability of the catalyst are evaluated in a fixed-bed reactor. When the reaction is carried out in a fixed-bed reactor, the liquid hourly space velocity is 0.05-5 h⁻¹. -1 Preferably 0.1-2h -1 The liquid phase refers to an aqueous solution of glycerol.
[0096] The present invention will be described in detail below through examples and comparative examples. Unless otherwise specified, the reagents and materials used in the following examples and comparative examples are commercially available, and the room temperature is 25°C.
[0097] The polyoxyethylene polyoxypropylene ether (Pluronic F127) was purchased from Aladdin, product number A196247.
[0098] Example 1
[0099] (1) Ammonium metatungstate was coated on the Al(OH)3 hydroxide core. The amount of ammonium metatungstate added was based on WO3. The mass ratio of WO3 to alumina was 1:19. The average particle size of the Al(OH)3 core was 0.5 μm. The core was subjected to a first heat treatment at 600℃ for 3 h to obtain a core containing W bimetallic oxide W-Al2O3.
[0100] (2) Take 100 mL of water and 100 mL of ethanol and place them in a 1 L round bottom flask. Add 0.1 g of Pt and 0.6 g of polyvinylpyrrolidone (PVP) through 8 wt% chloroplatinic acid solution. Stir for 5 minutes, then heat to 100 °C and reflux for 3 hours under an argon atmosphere to obtain a Pt nanoparticle solution.
[0101] Add 5g of the core containing W bimetallic oxide to 200mL of the above Pt nanoparticle solution, stir under ultrasonic conditions for 3 hours, centrifuge, and then perform a second heat treatment at 80℃ for 6 hours to obtain W-A2O3@Pt loaded with Pt nanoparticles.
[0102] (3) 1.5 g of triblock copolymer polyoxyethylene-polyoxypropylene ether (Pluronic F127), 2.4 mL of acetic acid, 3.2 mL of concentrated hydrochloric acid, and 1 g of tetrabutyl titanate were gradually added to 30 mL of tetrahydrofuran. After vigorous stirring for 10 minutes, the mixture was placed in an oven at 45 °C and allowed to stand for 24 hours to slowly evaporate the tetrahydrofuran solvent. A white-yellow polyoxyethylene-polyoxypropylene ether / TiO2 composite monomer micelle gel was obtained. 3 g of the gel formed above and 3 mL of trimethylbenzene were redispersed in 10 mL of anhydrous ethanol and stirred for 10 minutes. Then, glycerol (10 mL) was added dropwise and stirred for 5 minutes to form a transparent solution. Then, anhydrous ethanol (2 mL) containing 1 g of W-A2O3@Pt bimetallic oxide loaded with Pt nanoparticles was added to the transparent solution. The entire solution was heated to 100 °C in an oil bath and gently stirred (350 rpm) for 6 hours. After cooling to room temperature, the solution was centrifuged and dried.
[0103] Finally, the dried product was calcined at 350°C for 3 hours under a nitrogen atmosphere to produce the W-A2O3@Pt@mTiO2 core-shell catalyst.
[0104] Figure 1 and Figure 2 These are transmission electron microscopy (TEM) and scanning electron microscopy (SEM) images of the W-Al2O3@Pt@m-TiO2 catalyst containing TiO2 nanofilms in Example 1. Figure 1 It can be seen from this that the catalyst has a uniform TiO2 shell, from Figure 2 It can be seen that the catalyst has ordered mesopores perpendicular to the catalyst surface.
[0105] Example 2
[0106] The catalyst was prepared according to the method of Example 1, except that Al(OH)3 was replaced with Zr(OH)4 in step (1) so that the mass of the first metal oxide in the catalyst was the same as in Example 1, and a W-ZrO2@Pt@mTiO2 core-shell structure catalyst was obtained.
[0107] Example 3
[0108] The catalyst was prepared according to the method of Example 1, except that the amount of ammonium metatungstate added was changed so that the mass ratio of WO3 to alumina was 1:25, the average particle size of aluminum hydroxide was 0.5 μm, and other conditions were the same as in Example 1, thus obtaining the W-Al2O3@Pt@m-TiO2 catalyst.
[0109] Example 4
[0110] (1) Ammonium metatungstate was coated on the Nb(OH)5 core. The amount of ammonium metatungstate added was based on WO3. The mass ratio of WO3 to Nb2O5 was 1:19. The average particle size of the core was 0.5 μm. The core was subjected to a first heat treatment at 500℃ for 3 h to obtain W-Nb2O5 core containing W bimetallic oxide.
[0111] (2) Take 20 mL of water and 180 mL of propanol and place them in a 500 mL round bottom flask. Add 0.2 g of Pt and 0.6 g of polyvinylpyrrolidone (PVP) through tetraammineplatinum nitrate (Pt source). Stir for 5 minutes, then heat to 90 °C and reflux for 3 hours under an argon atmosphere to obtain a Pt nanoparticle solution.
[0112] 10g of the core containing W bimetallic oxide was added to the above 200mL Pt nanoparticle solution, stirred under ultrasonic conditions for 3 hours, centrifuged, and then subjected to a second heat treatment at 80℃ for 5 hours to obtain W-Nb2O5@Pt loaded with Pt nanoparticles.
[0113] (3) 1.8 g of triblock copolymer polyoxyethylene-polyoxybutylene ether, 2.6 mL of acetic acid, 3.0 mL of concentrated hydrochloric acid, and 1.38 g of tetrabutyl titanate were gradually added to 30 mL of tetrahydrofuran. After vigorous stirring for 10 minutes, the mixture was placed in an oven at 45 °C and allowed to stand for 24 hours to slowly evaporate the tetrahydrofuran solvent. A white-yellow polyoxyethylene-polyoxypropylene ether / TiO2 composite monomer micelle gel was obtained. 3 g of the gel formed above and 3 mL of trimethylbenzene were redispersed in 10 mL of anhydrous ethanol and stirred for 10 minutes. Then, glycerol (10 mL) was added dropwise and stirred for 5 minutes to form a transparent solution. Then, anhydrous ethanol (2 mL) containing 1 g of W bimetallic oxide loaded with Pt nanoparticles was added to the mixture. The entire solution was heated to 95 °C in an oil bath and stirred gently (350 rpm) for 8 hours. After cooling to room temperature, the solution was centrifuged and dried.
[0114] The dried product was calcined at 450℃ for 4 hours under a nitrogen atmosphere to obtain a W-Nb2O5@Pt@mTiO2 core-shell catalyst.
[0115] Example 5
[0116] The catalyst was prepared according to the method of Example 1, except that in step (2), Pt nanoparticles were loaded onto the core containing W bimetallic oxide using the equal volume impregnation method. Specifically, 1 g of the core W-A2O3 containing W bimetallic oxide obtained in step (1) was impregnated with 1.3 mL of a solution containing 0.015 g of Pt nanoparticles, and then subjected to a second heat treatment at 80 °C for 6 hours. Other conditions were the same as in Example 1 to obtain the catalyst.
[0117] Example 6
[0118] The catalyst was prepared according to the method of Example 1, except that step (1) was omitted. Instead, ammonium metatungstate of the same mass as in Example 1 was directly added to the Pt nanoparticle solution in step (2) and loaded onto an aluminum hydroxide core of the same mass as in Example 1. Other conditions were the same as in Example 1 to obtain the catalyst.
[0119] Example 7
[0120] The catalyst was prepared according to the method of Example 1, except that the amount of ammonium metatungstate added was changed so that the mass ratio of WO3 to alumina was 1:9, the average particle size of alumina was 0.5 μm, and other conditions were the same as in Example 1, thus obtaining the W-Al2O3@Pt@m-TiO2 catalyst.
[0121] Example 8
[0122] The catalyst was prepared according to the method of Example 1, except that the amount of titanium source added in step (3) was increased so that the thickness of the TiO2 nanofilm was 62 nm. Other conditions were the same as in Example 1, and W-Al2O3@Pt@m-TiO2 catalyst was obtained.
[0123] Comparative Example 1
[0124] The catalyst was prepared according to the method of Example 1, except that step (3) was omitted. Instead, the W-containing bimetallic oxide loaded with Pt nanoparticles from step (2) was directly centrifuged, dried, and calcined, with other conditions the same as in Example 1, to obtain the catalyst.
[0125] Comparative Example 2
[0126] The catalyst was prepared according to the method of Example 1, except that tetrabutyl titanate was not added in step (3), and the other conditions were the same as in Example 1. TiO2 nanofilm could not be formed.
[0127] Test case
[0128] The structural parameters and active component contents of the catalysts prepared in the examples and comparative examples are shown in Table 1.
[0129] Table 1
[0130]
[0131] Note: / indicates that no relevant tests were conducted.
[0132] Weigh 1g of the catalyst obtained in the examples and comparative examples, place it in a fixed-bed reactor, and react it at a temperature of 160°C and a hydrogen pressure of 4MPa. The mass hourly space velocity (WHSV) of the glycerol aqueous solution is 1h. -1 A 50wt% aqueous glycerol solution was introduced, and the liquid from the outlet was collected after 8 hours and 360 hours of reaction for gas chromatography analysis. The results are shown in Table 2.
[0133] Table 2
[0134]
[0135] As can be seen from Table 1, the Pt content of the core-shell structured catalyst prepared in the examples hardly changed before and after the reaction, while the Pt content of the comparative catalyst without shell protection was lost by 8 wt% after 360 h of reaction.
[0136] As can be seen from the results in Table 2, the catalyst prepared using the embodiments of the present invention, when used for the hydrogenolysis of glycerol to 1,3-propanediol, exhibits higher hydrothermal stability compared to catalysts synthesized by existing methods. It can suppress the loss and aggregation of Pt, and significantly improves the glycerol conversion rate and the selectivity of 1,3-propanediol in the product. Furthermore, after 360 hours of operation, the activity of the core-shell structure catalyst in the embodiments only decreased slightly, while the activity of the comparative catalyst without the shell decreased by 50%, indicating that the multilayer core-shell structure catalyst has excellent stability.
[0137] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A core-shell structured catalyst, characterized in that, The catalyst comprises a core, a sandwich layer, and a shell; The catalyst has a core containing a W-containing bimetallic oxide, an interlayer containing Pt nanoparticles, and an outer shell containing a TiO2 nanofilm.
2. The catalyst according to claim 1, wherein, The W-containing bimetallic oxide comprises a W oxide and a first metal oxide; Preferably, the first metal oxide is selected from at least one of aluminum oxide, zirconium oxide, and niobium oxide; Preferably, the average particle size of the catalyst core is 0.1-10 μm, more preferably 0.2-2 μm; Preferably, the W oxide content is 0.5-10 wt% by mass, more preferably 2-6 wt%, based on the total mass of the catalyst.
3. The catalyst according to claim 1 or 2, wherein, The average particle size of the Pt nanoparticles in the interlayer is 0.5-6 nm, preferably 2-4 nm; Preferably, the Pt nanoparticles have a mass percentage content of 0.2-4 wt%, more preferably 1-2 wt%, based on the total mass of the catalyst.
4. The catalyst according to any one of claims 1-3, wherein, The thickness of the TiO2 nanofilm in the outer shell is 0.1-80 nm, preferably 5-50 nm; Preferably, the TiO2 nanofilm has mesoporous structures; Preferably, the average pore size of the TiO2 nanofilm is 2-12 nm, and more preferably 6-10 nm.
5. A method for preparing a core-shell structured catalyst, characterized in that, The method includes: (1) Load W onto the first metal hydroxide and perform a first heat treatment to obtain a W-containing bimetallic oxide; (2) Load Pt nanoparticles onto W-containing bimetallic oxides to obtain W-containing bimetallic oxides loaded with Pt nanoparticles. (3) Mix the W-containing bimetallic oxide loaded with Pt nanoparticles with the interface assembly solution to carry out the synthesis reaction to obtain the intermediate product, and calcine the intermediate product to obtain the core-shell structure catalyst with TiO2 nanofilm shell.
6. The method according to claim 5, wherein, The first metal hydroxide is selected from at least one of aluminum hydroxide, niobium hydroxide, and zirconium hydroxide; Preferably, in step (1), the loading method includes: coating the W precursor onto a first metal hydroxide, performing a first heat treatment, and obtaining a W-containing bimetallic oxide; Preferably, the W precursor is selected from at least one of ammonium metatungstate, ammonium paratungstate, and sodium tungstate; Preferably, the amount of the W precursor added is calculated as WO3, the amount of the first metal hydroxide used is calculated as oxide, and the ratio of the amount of the W precursor to the amount of the first metal hydroxide used is 1:5-50, preferably 1:10-30. Preferably, the conditions for the first heat treatment include: a heating temperature of 100-900℃, more preferably 500-600℃; and a heating time of 1-8h, more preferably 2-4h.
7. The method according to claim 5 or 6, wherein, In step (2), the loading method includes: mixing a W-containing bimetallic oxide and a Pt-containing nanoparticle solution and performing a second heat treatment to obtain a W-containing bimetallic oxide loaded with Pt nanoparticles; Preferably, the mass ratio of the W-containing bimetallic oxide to the Pt nanoparticles is 1:0.002-0.04, more preferably 1:0.01-0.02; Preferably, the conditions for the second heat treatment include: a heating temperature of 40-120°C, more preferably 60-100°C; and a heating time of 1-15 hours, more preferably 3-10 hours.
8. The method according to claim 7, wherein, The method for preparing the Pt nanoparticle-containing solution includes: mixing a Pt source, a first template agent, and a first solvent, and then refluxing the mixture to obtain a Pt nanoparticle solution; Preferably, the amount of Pt source used is calculated based on Pt element, and the mass ratio of Pt source: first template agent: first solvent is (1-5):(5-50):(500-10000), preferably (2-4):(10-30):(1000-5000); Preferably, the reflux conditions include: under a protective atmosphere, a reflux temperature of 60-200℃, preferably 80-180℃; and a reflux time of 0.5-6h, preferably 2-4h. Preferably, the Pt source is selected from at least one of chloroplatinic acid, tetraammineplatinum nitrate, and potassium chloroplatinate; Preferably, the first template agent is selected from at least one of polyvinylpyrrolidone, polyethyleneimine, and oleylamine; Preferably, the first solvent is selected from at least one of water, a saturated monohydric alcohol having 1-3 carbon atoms, and a saturated dihydric alcohol having 1-3 carbon atoms.
9. The method according to any one of claims 6-8, wherein, In step (3), the intermediate product is synthesized by a confined interface single micromicelle assembly method; Preferably, the interface assembly solution comprises a second template agent, a first acid, a second acid, a titanium source, and a second solvent; Preferably, in the interface assembly solution, the mass ratio of the second template agent: the first acid: the second acid: the titanium source: the second solvent is 1:(0.1-10):(0.1-10):(0.1-10):(1-100), more preferably 1:(1-3):(1-5):(0.5-7):(2-50); Preferably, the second template agent is selected from at least one of polyoxyethylene-polyoxypropylene ether, polyoxyethylene-polyoxybutylene ether, and polyoxyethylene-polyoxypropylene. Preferably, the titanium source is selected from at least one of tetrabutyl titanate, tetraethyl titanate, and tetraoctyl titanate; Preferably, the synthesis conditions include: a reaction temperature of 80-180℃, more preferably 100-160℃; and a reaction time of 2-12h, more preferably 4-8h. Preferably, the calcination conditions include: a calcination temperature of 200-600℃, more preferably 300-500℃; and a calcination time of 1-10h, more preferably 3-6h.
10. The catalyst prepared by the method according to any one of claims 5-9.
11. The use of the catalyst according to any one of claims 1-4, 10 in the synthesis of 1,3-propanediol.
12. A method for synthesizing 1,3-propanediol from glycerol, characterized in that, The method comprises: contacting glycerol and hydrogen in the presence of the catalyst described in any one of claims 1-4 and 10 to carry out a hydrogenolysis reaction; Preferably, the reaction conditions include: a reaction temperature of 120-200℃, more preferably 130-170℃, and a hydrogen pressure of 1-6MPa, more preferably 3-5MPa; And / or, the reaction conditions include: a reaction time of 4-500 h, preferably 8-360 h; Preferably, the glycerol is added in the form of an aqueous glycerol solution, wherein the concentration of glycerol in the aqueous glycerol solution is 10-90 wt%, preferably 30-80 wt%. Preferably, when the reaction is carried out in a fixed-bed reactor, the liquid hourly space velocity (LHSV) is 0.05-5 h⁻¹. -1 Preferably 0.1-2h -1 .
Citation Information
Patent Citations
Process for the biological production of 1,3-propanediol with high yield
CN100471946C
